1998
DOI: 10.1016/s0014-5793(98)00866-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and functional expression of dihydroxypterocarpan 6a‐hydroxylase, an enzyme specific for pterocarpanoid phytoalexin biosynthesis in soybean (Glycine max L.)

Abstract: Four cytochrome P450-dependent enzymes, among them dihydroxypterocarpan 6a-hydroxylase (D6aH), are specifically involved in the elicitor-inducible biosynthesis of glyceollins, the phytoalexins of soybean. Here we report that CYP93A1 cDNA, which we isolated previously from elicitor-induced soybean cells, codes for a protein with D6aH activity. Analysis of the catalytic properties of recombinant CYP93A1 expressed in yeast, its NADPH dependency, stereoselectivity and high substrate affinity confirmed that D6aH is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 18 publications
(36 reference statements)
0
44
0
Order By: Relevance
“…In glyceollin I biosynthesis, the direct flavonoid substrate of G4DT is produced at the ER by the P450 3,9-dihydroxypterocarpan 6a-hydroxylase (Schopfer et al, 1998), and the product of G4DT supplies the substrate of another P450 enzyme, a cyclase, in the ER again (Welle and Grisebach, 1988). Although the physiological meaning of the intracellular movement of biosynthetic intermediates is unknown, the present study may enable the characterization the P450 cyclase at the molecular level by providing the appropriate substrate.…”
Section: Plastid Localization Of Flavonoid Prenyltransferasesmentioning
confidence: 87%
“…In glyceollin I biosynthesis, the direct flavonoid substrate of G4DT is produced at the ER by the P450 3,9-dihydroxypterocarpan 6a-hydroxylase (Schopfer et al, 1998), and the product of G4DT supplies the substrate of another P450 enzyme, a cyclase, in the ER again (Welle and Grisebach, 1988). Although the physiological meaning of the intracellular movement of biosynthetic intermediates is unknown, the present study may enable the characterization the P450 cyclase at the molecular level by providing the appropriate substrate.…”
Section: Plastid Localization Of Flavonoid Prenyltransferasesmentioning
confidence: 87%
“…G4DT was shown to localize at the plastids (Akashi et al 2009), similar to other flavonoid prenyltransferases identified to date ). However, glycinol is biosynthesized by 3,9-dihydroxypterocarpan 6a-hydroxylase, a cytochrome P450 localized at the ER (Schopfer et al 1998), suggesting an as yet uncharacterized mechanism of glycinol transport into the plastids. Moreover, 4-dimethylallylglycinol, the product of G4DT, is cyclized by another cytochrome P450 localized at the ER (Welle and Grisebach 1988).…”
Section: Interactions With Pathogensmentioning
confidence: 99%
“…Previous analyses of the catalytic properties of recombinant proteins expressed in yeast disclosed the function of two of the clones. CYP73A11 cDNA encoded a cinnamate 4-hydroxylase (17), whereas CYP93A1 cDNA coded for 3,9-dihydroxypterocarpan 6a-hydroxylase (18). The former cytochrome P-450 thus represented a well studied enzyme of general phenylpropanoid metabolism whose action gives rise to the hydroxyl group in position 4Ј of the flavonoid B-ring.…”
Section: Flavonoid 6-hydroxylase Cyp71d9 From Soybeanmentioning
confidence: 99%
“…Eight full-length cDNA clones were subsequently isolated that represented elicitor-activated cytochromes P-450. One of these, CYP73A11 cDNA, encoded cin-namate 4-hydroxylase, and a second one, CYP93A1 cDNA, coded for 3,9-dihydroxypterocarpan 6a-hydroxylase (17,18).…”
mentioning
confidence: 99%